The Impact of School Climate and School Identification on Academic Achievement: Multilevel Modeling with Student and Teacher Data - Maxwell, Sophie; Reynolds, Katherine J.; Lee, Eunro; Subasic, Emina; Bromhead, David (Frontiers in Psychology, 2017)
School climate is a leading factor in explaining student learning and achievement. Less work has explored the impact of both staff and student perceptions of school climate raising interesting questions about whether staff school climate experiences can add “value” to students’ achievement. In the current research, multiple sources were integrated into a multilevel model, including staff self-reports, student self-reports, objective school records of academic achievement and socio-economic demographics. Achievement was assessed using a national literacy and numeracy tests (N = 760 staff and 2,257 students from 17 secondary schools). In addition, guided by the ‘social identity approach’, school identification is investigated as a possible psychological mechanism to explain the relationship between school climate and achievement. In line with predictions, results show that students’ perceptions of school climate significantly explain writing and numeracy achievement and this effect is mediated by students’ psychological identification with the school. Furthermore, staff perceptions of school climate explain students’ achievement on numeracy, writing and reading tests (while accounting for students’ responses). However, staff’s school identification did not play a significant role. Implications of these findings for organizational, social, and educational research are discussed.